Stomatal and Morphological Characteristics of In-Vitro Grown Tomato (Solanum lycopersicum L.) Treated with Different Concentrations of Colchicine and Pendimethalin - Jessa R. Gines; Catherine C. Arradaza; Marilyn M. Belarmino; Marilou M. Benitez; Rosemarie B. Gonzaga (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This research investigated the stomatal and morphological response of in vitro grown tomato (Solanum lycopersicum L.) plantlets to different concentrations of colchicine and pendimethalin. The effects of treatments on stomatal parameters, chlorophyll content and morphological characteristics were studied. The study was conducted using a Completely Randomized Design (CRD) with seven treatments replicated three times with ten samples per replicate at the Plant Tissue Culture Laboratory, Department of Horticulture, Visayas State University. To evaluate the responses of various concentrations of colchicine (1.5, 3.0 and 5.0 mM) and pendimethalin (10, 20 and 30 µM), induced polyploid-associated traits and overall plant growth and development rate on tomato plantlets have also been compared with normal diploid plantlet used as control in subsequent measurement. The results indicated that the mutagen treatments have a substantial effect on explant viability, stomatal traits and chlorophyll content as well as vegetative growth of tomato plants. Moderate concentrations had more profound effect with higher survival percentages of explants found for 20 µM pendimethalin (91%) and 5.0 mM colchicine (84%), which produced regeneration and adaptation, as compared to other concentrations in this study. It was found out with an increased stomatal length, width and aperture on mutation treated plantlets but decreased stomatal density shows induction of polyploid trait. Colchicine resulted in the greatest stomatal size together with favourable impact on chlorophyll content. In contrast, at the highest concentrations of pendimethalin (30 µM), growth was inhibited and chlorophyll was decreased as a result of phytotoxicity.